Diffraction by a Thick Half Plane Composed of PEMC Metamaterial - Naeemul Haq; A.B. Mann; Saeed Ahmed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Diffraction of a plane wave by a thick half plane composed of metamaterial was examined by employing duality transformation proposed by Lindell and Sihvola [18, 20, 21, 24]. As perfect electric conductor (PEC) and perfect magnetic conductor (PMC) media can both be derived as limiting cases of perfect electromagnetic conductor medium, so it was thought worthwhile to attempt and generalize the problem of diffraction by a thick PEC half plane to thick PEMC half plane. The boundary value problem was solved by using an integral transform, the Wiener-Hopf (WH) technique and the method of steepest descent. Infinite algebraic equations, containing infinite constants, arose in the problem under consideration which were solved numerically. The effects of arising parameters of thickness and admittance on amplitude of the diffracted field were plotted and are discussed.